A very serious thing : women's humor and American culture - Walker, Nancy A., 1942- (American culture (Minneapolis, Minn.) ;, 1988)
Defines why women have been blocked from participating in the mainstream of American comedy yet have overcome hurdles to produce a humor that is sustaining and spells survival for women in society.